2022
DOI: 10.3390/children9071071
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Individual- and Community-Level Variability in Predictors of Neonatal, Infant, and Under-Five Child Mortality in Ethiopia Using a Multilevel Modeling Approach

Abstract: Background: In low-and middle-income countries, child mortality rates are basic indicators of a country’s socio-economic situation and quality of life. The Ethiopian government is currently working to reduce child mortality to accomplish its long-term development goals. Using data from the Ethiopian Mini Demographic and Health Survey, 2019, this study analyzed the determinants of child mortality in Ethiopia. Methods: A total of 4806 children were considered in the final analyses. Multivariate analysis was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…The findings on the association of wait period prior to the index birth and infant mortality are in agreement with findings of studies by Wardani et al (2022) and Kuse et al (2022). A study by Wardani et al (2022) found the risk of infant mortality with a preceding birth interval of ≥ 24 months to be lower than that with a preceding birth interval of < 24 months (aOR = 0.48; CI = 0.26 -0.90).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The findings on the association of wait period prior to the index birth and infant mortality are in agreement with findings of studies by Wardani et al (2022) and Kuse et al (2022). A study by Wardani et al (2022) found the risk of infant mortality with a preceding birth interval of ≥ 24 months to be lower than that with a preceding birth interval of < 24 months (aOR = 0.48; CI = 0.26 -0.90).…”
Section: Discussionsupporting
confidence: 89%
“…These results are consistent with those of other studies (Ikamari, Imbo, Mbuthia and Ngotho (2021) found mothers with no education to have had higher odds of experiencing neonatal mortality (aOR = 2.201; ρ <0.05; CI = 1.43 -4.15) compared to mothers with higher education. Neonatal mortalities for mothers with secondary and higher educational levels were about 22 percent and 46 percent less likely compared to those of mothers with no education, respectively (Kuse et al, 2022). The odds of infant mortality decreased by 64 percent, 88 percent and 82 percent respectively, for mothers with primary, secondary, and higher educational levels with reference to their colleagues with no any education qualifications.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The main limitation of this study that the EMDHS is mostly based on respondents' self-report and might have the possibility of recall bias. In addition, variables such as weight at birth [48,55,56], anemia status of mother [56][57][58], breastfeeding status of child [7,48,59], diarrhea [49,60,61], desire of pregnancy [62][63][64][65], employment status of mother [49,66,67], educational level of father [68][69][70] and maternal HIV status [71][72][73] were not included in the study due to large number of missing values/unavailability in the dataset.…”
Section: Strength and Limitations Of The Studymentioning
confidence: 99%